COMPORTAMENTO ORGANIZACIONAL - A PERCEPÇÃO DA ESPIRITUALIDADE COMO FATOR DE INFLUÊNCIA NA MOTIVAÇÃO E NA QUALIDADE DE VIDA DO TRABALHADOR: UM ESTUDO DE CASO COM SECRETÁRIOS-EXECUTIVOS DO ESTADO DO RIO DE JANEIRO. - Marson, Luciana Sousa Coelho (2009)
The search to identify the factors that provide human motivation have been constant within the organizational context, and to continue these studies to this research proposal is to investigate how the issue of perception of spirituality can contribute positively to influence worker behavior. The basis of this study was the theoretical framework of Zohar and Marshall (2002), and Rego, Souto and Cunha (2004) precursors in empirical studies of organizational and individual spirituality. The aspects of perception, culture, motivation and quality of work life, were also part of the literature review, thus enabling pave the way for the development of analysis with the interviews. The research was conducted through a questionnaire with closed questions and treated in a quantitative manner, and they had interviewed as executive secretaries of the state of Rio de Janeiro. The results were displayed through charts and tables that show the rates of concordance for each variable. These indices indicate that an individual with developed spirituality may have stronger motivation and therefore better quality of life at work. It was found that the aspects of teamwork and helping others obtained the highest rates of agreement. The spirituality in organizations needs to be separated from religion to have greater acceptance, and thus provide better results for both people and for businesses.